2014
DOI: 10.1053/j.gastro.2013.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations in Oncogene-Induced Senescence Pathways Are Associated With Multiple Sessile Serrated Adenomas

Abstract: Background & Aims Little is known about the genetic factors that contribute to development of sessile serrated adenomas (SSAs). SSAs contain somatic mutations in BRAF or KRAS early in development. However, evidence from humans and mouse models indicates that these mutations result in oncogene-induced senescence (OIS) of intestinal crypt cells. Progression to serrated neoplasia requires cells to escape OIS, via inactivation of tumor suppressor pathways. We investigated whether individuals with multiple SSAs car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 64 publications
5
109
4
5
Order By: Relevance
“…58 A number of mutations in genes resulting in oncogene-induced senescence have also been associated with sessile serrated adenomas. 59 These mechanisms could be considered in future searches of gallstone formation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…58 A number of mutations in genes resulting in oncogene-induced senescence have also been associated with sessile serrated adenomas. 59 These mechanisms could be considered in future searches of gallstone formation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study reported germline mutations in genes in the "oncogene-induced senescence" pathway, 52 and Cowden Syndrome and biallelic MutYH mutations have been reported in some individuals meeting WHO criteria for serrated polyposis, 53 clinical genetic testing has a low yield.…”
Section: Hamartomatous Polyposis Syndromesmentioning
confidence: 99%
“…BRAF mutations have been identified in the majority of lesions, but mutations in the KRAS gene also occur [54]. Very recently, germline mutations in genes that regulate senescence pathways (ATM, PIF1, TELO2, XAF1, and RBL1) have been associated with the occurrence of multiple SSA/Ps and the serrated polyposis syndrome [55], but data are still limited.…”
Section: Serrated Lesionsmentioning
confidence: 99%